Subclass analysis of donor HLA‐specific IgG in antibody‐incompatible renal transplantation reveals a significant association of IgG4 with rejection and graft failure. (1st September 2015) - Khovanova, Natasha; Daga, Sunil; Shaikhina, Torgyn; Krishnan, Nithya; Jones, James; Zehnder, Daniel; Mitchell, Daniel; Higgins, Robert; Briggs, David; Lowe, David
Summary: Donor HLA‐specific antibodies (DSAs) can cause rejection and graft loss after renal transplantation, but their levels measured by the current assays are not fully predictive of outcomes. We investigated whether IgG subclasses of DSA were associated with early rejection and graft failure. DSA levels were determined pretreatment, at the day of peak pan‐IgG level and at 30 days post‐transplantation in eighty HLA antibody‐incompatible kidney transplant recipients using a modified microbead assay. Pretreatment IgG4 levels were predictive of acute antibody‐mediated rejection ( P = 0.003) in the first 30 days post‐transplant. Pre‐treatment presence of IgG4 DSA ( P = 0.008) and day 30 IgG3 DSA ( P = 0.03) was associated with poor graft survival. Multivariate regression analysis showed that in addition to pan‐IgG levels, total IgG4 levels were an independent risk factor for early rejection when measured pretreatment, and the presence of pretreatment IgG4 DSA was also an independent risk factor for graft failure. Pretreatment IgG4 DSA levels correlated independently with higher risk of early rejection episodes and medium‐term death‐censored graft survival. Thus, pretreatment IgG4 DSA may be used as a biomarker to predict and risk stratify cases with higher levels of pan‐IgG DSA in HLA antibody‐incompatible transplantation. Further investigations are needed to confirm our results.